2020
DOI: 10.2144/fsoa-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thrombocytopenia is Associated with Improved Survival in Patients Treated with Immunotherapy

Abstract: Background: Immune-related adverse events are associated with efficacy of immune checkpoint inhibitors (ICIs). We hypothesize that immune-mediated thrombocytopenia could be a biomarker for response to ICIs. Materials & methods: This retrospective study included 215 patients with metastatic malignancies treated with ICIs. Patients were stratified by nadir platelet count. Outcomes of interest were progression-free survival and overall survival. Results: On multivariate analysis, grade 1 thrombocytopenia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…One final provocative point is the observation of a potential correlation between irAE and improved clinical outcomes; 36 it has been posited that ir-TCP may be associated with improved clinical outcomes. 37 One of our patients (case 5) did indeed have an exceptional response to immunotherapy and remains in complete response from his metastatic colorectal cancer 18 months after the last cycle of pembrolizumab. In conclusion, ir-TCP is an uncommon entity which requires prompt recognition and individualized management in order to avoid interruption of therapy.…”
Section: Discussionmentioning
confidence: 73%
“…One final provocative point is the observation of a potential correlation between irAE and improved clinical outcomes; 36 it has been posited that ir-TCP may be associated with improved clinical outcomes. 37 One of our patients (case 5) did indeed have an exceptional response to immunotherapy and remains in complete response from his metastatic colorectal cancer 18 months after the last cycle of pembrolizumab. In conclusion, ir-TCP is an uncommon entity which requires prompt recognition and individualized management in order to avoid interruption of therapy.…”
Section: Discussionmentioning
confidence: 73%
“…Although only a small proportion of cancer cells express PD‐L1 on their surface, a 2–4‐fold increase in the number of cancer cells expressing it, caused by platelets, likely reflects a highly significant effect size considering that metastasis is an extremely inefficient and selective process in which less than 0.01% of circulating cancer cells succeed 28,29 . In support of such a view is a recent study demonstrating that among urothelial carcinoma patients PD‐L1 positivity was associated with shorter metastasis‐free and overall survival in those with high platelet counts, 30 while another study of patients with metastatic malignancies treated with immune checkpoint inhibitors showed that a mild thrombocytopenia (grade 1; nadir platelet count 75–150 × 10 3 μl −1 blood) was associated with increased overall survival compared with non‐thrombocytopenic patients 31 . Using platelets derived from healthy donors we showed that platelets increase cancer cell PD‐L1 mRNA in addition to surface protein.…”
Section: Discussionmentioning
confidence: 92%
“…28,29 In support of such a view is a recent study demonstrating that among urothelial carcinoma patients PD-L1 positivity was associated with shorter metastasis-free and overall survival in those with high platelet counts, 30 while another study of patients with metastatic malignancies treated with immune checkpoint inhibitors showed that a mild thrombocytopenia (grade 1; nadir platelet count 75-150 × 10 3 μl −1 blood) was associated with increased overall survival compared with non-thrombocytopenic patients. 31 Using platelets derived from healthy donors we showed that platelets increase cancer cell PD-L1 mRNA in addition to surface protein.…”
Section: Discussionmentioning
confidence: 94%
“…Generally, other irAEs have been shown to be associated with the efficacy of PD-1/PD-L1 inhibitors in patients with lung cancer ( 28 , 29 ). Same as other irAEs, grade 1 thrombocytopenia during ICIs therapy is positively associated with Overall survival (OS), but lacks of Progression-free survival (PFS) benefit ( 30 ). Immune thrombocytopenia usually is not fatal, but deaths caused by the adverse events had been reported in uncommon cases ( 25 ).…”
Section: Epidemiology Of Icis-induced Thrombocytopeniamentioning
confidence: 99%